Corticospinal and spinal adaptations to motor skill and resistance training: Potential mechanisms and implications for motor rehabilitation and athletic development - Tallent, J.; Woodhead, A.; Frazer, A. K.; Hill, J.; Kidgell, D. J.; Howatson, G. (European Journal of Applied Physiology, 2021)
Optimal strategies for enhancing strength and improving motor skills are vital in athletic performance and clinical rehabilitation. Initial increases in strength and the acquisition of new motor skills have long been attributed to neurological adaptations. However, early increases in strength may be predominantly due to improvements in inter-muscular coordination rather than the force-generating capacity of the muscle. Despite the plethora of research investigating neurological adaptations from motor skill or resistance training in isolation, little effort has been made in consolidating this research to compare motor skill and resistance training adaptations. The findings of this review demonstrated that motor skill and resistance training adaptations show similar short-term mechanisms of adaptations, particularly at a cortical level. Increases in corticospinal excitability and a release in short-interval cortical inhibition occur as a result of the commencement of both resistance and motor skill training. Spinal changes show evidence of task-specific adaptations from the acquired motor skill, with an increase or decrease in spinal reflex excitability, dependant on the motor task. An increase in synaptic efficacy of the reticulospinal projections is likely to be a prominent mechanism for driving strength adaptations at the subcortical level, though more research is needed. Transcranial electric stimulation has been shown to increase corticospinal excitability and augment motor skill adaptations, but limited evidence exists for further enhancing strength adaptations from resistance training. Despite the logistical challenges, future work should compare the longitudinal adaptations between motor skill and resistance training to further optimise exercise programming.